COVID-19 vaccination in patients with cancer receiving immune checkpoint inhibitors: a systematic review and meta-analysis. Issue 2 (6th February 2023) - Ruiz, Juan Ignacio; Lopez-Olivo, Maria Angeles; Geng, Yimin; Suarez-Almazor, Maria E
Abstract : Background: Immune checkpoint inhibitors (ICI) can cause off-target inflammatory and immune-related adverse events (irAE). Conceivably, COVID-19 vaccination could trigger an inflammatory and immune response that could induce or aggravate irAE. Methods: The objective of this systematic review is to appraise the efficacy and safety of COVID-19 vaccination in patients with cancer treated with ICI. The literature search was performed in PubMed and Embase in English from December 2019 to February 2022. The review included clinical trials, observational cohort studies, case series, and case reports reporting on the clinical efficacy and safety of COVID-19 vaccines on patients with cancer treated with ICI. Outcomes of interest included seroconversion, SARS-CoV-2 infection rate, severe COVID-19, COVID-19 mortality rate. Incidence of ICI irAEs was also ascertained as well as vaccine adverse events. A meta-analysis was conducted to estimate the pooled effect sizes of the outcomes when possible, using random effects models. Results: Overall, 19 studies were included for the analysis (n=10 865 with 2477 receiving ICI). We analyzed 15 cohort studies, 1 cross-sectional study, and 3 case reports. There were no statistically significant differences in seroconversion rates after the second dose of the vaccine when comparing patients with cancer receiving ICI with patients without cancer (risk ratio, RR 0.97, 95% CI 0.92 to 1.03) or with patients with cancer without active treatment (RR 1.00, 95% CI 0.96 to 1.04). There was a higher probability of seroconversion in patients with cancer treated with ICI compared with patients with cancer treated with chemotherapy (RR 1.09, 95% CI 1.00 to 1.18). In a single study in patients receiving ICI, no differences were observed in risk of irAE between those receiving inactivated vaccine and those unvaccinated (pneumonitis RR 0.88, 95% CI 0.33 to 2.3; rash RR 1.03, 95% CI 0.66 to 1.62; arthralgia RR 0.94, 95% CI 0.51 to 1.75). There were no studies for other types of vaccines comparing vaccinated vs not vaccinated in patients treated with ICI. The most common vaccine-related adverse events were local pain or fatigue. Overall, the quality of evidence was rated as very low. Conclusion: COVID-19 vaccination appears to be effective and safe in patients with cancer receiving ICI.